Isolasi dan Identifikasi Bakteri Clostridium Botulinum pada Minyak Jelantah - Asti Hanipah; Kartika Manalu; Rizki Amelia Nasution (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The aims of this study were to determine whether Clostridium botulinum bacteria were present in used cooking oil, and to look at the characteristics of Clostridium botulinum bacteria in used cooking oil. In this study, isolation of bacteria from used cooking oil using blood agar media, identification of bacteria using gram staining and biochemical tests such as gelatin test, triple sugar iron agar (TSIA) test, simon citrate test, and motility test were carried out. The results of the study obtained 2 out of 3 samples containing Clostridium botulinum bacteria. These bacteria are more common in used cooking oil, which has a more blackish brown color, lots of crumbs left over from food, and temperatures around 30-55â„ƒ. In conclusion, there is Clostridium botulinum bacteria found in used cooking oil. Clostridium botulinum colonies are grey, alpha hemolytic, circular to irregular in shape with scalloped edges or rhizoids, and flat to raised surfaces. Keywords: Clostridium botulinum, Isolation, Identification, Cooking Oil